Martha Graham, ‘An American, A kosmos’: Border-crossing in Martha Graham’s early works - Adeline CHEVRIER-BOSSEAU (E-REA)
This paper examines the connection between crossing borders (state limits, borders between America and Mexico or America and Europe, and temporal borders) and pushing choreographical boundaries in dance pioneer Martha Graham’s ballets created in the 1930’s and the early 1940’s.Danced only by women, Primitive Mysteries (1931) was inspired by Graham’s travels in New Mexico, and explores the rituals of the Native Americans of the Southern States of the United States; nine years later, Graham would explore this theme further with El Penitente, which also draws from the Medieval tradition of mystery plays. Frontier (1935), one of Graham’s most famous soli, clearly connects the American Frontier to the construction of female identity, as do American Document (1938) and Appalachian Spring (1944). Graham pioneered a new way for women to dance, to express their femininity and their power: her works, inspired by Native American traditions, Mexican folklore, Greek mythology and literature from both sides of the Atlantic, depict strong women who are not afraid of pushing boundaries.Creating an American choreographic tradition also meant exploring its literary legacy for Martha Graham: this paper therefore also delves into the way the Whitmanian intertext emerges in Graham’s choreographic writing, in her conception of Americanness, modernity, the body and gender.